Quarrying induced particulate air pollution in Jaipur City, western India - Das, D. B.; Bhargava, Akshey; Kushwaha, R. K.; Gupta, A. B.; Pandit, M. K. (Journal of Nepal Geological Society, 1998)
Jhalana hills, fringing the northern and northeastern periphery of the Jaipur City in Rajasthan, western India, form a part of Aravalli bill Range. Stratigrapbically, they belong to the Middle Proterozoic, Delhi Supergroup of rocks, predominantly comprising of quartzite indicating arenaceous facies sedimentation. Signatures of polypbase deformation are manifested as tight to isoclinal folds and steep dips. On account of its close vicinity to the city and conforming to various structural engineering standards, the Jhalana Quartzite bas been a source of construction material for the last two centuries for all types of civil engineering activities in and around Jaipur. Rapid and unplanned urbanisation of Jaipur and the hinterland areas bas resulted in urban sprawl and industrialization. Increased demand for construction material has resulted in multifold rise in quarrying operations, without taking into account of the consequent adverse impacts. This has led to alarming increase in suspended particulate matter (SPM) in air as one of the three major air pollutants in Jaipur, besides sulphur dioxide (SO2) and nitrogen oxides (NO2). The present work focuses on monitoring and quantitative evaluation of air quality in relation to quarrying activity. The observed values have been compared with the prescribed SPM limits for impact assessment. The air quality monitoring bas been carried out by establishing three observation sites at different directions from the source of pollution (quarries and stone crusher sites). The prevailing wind direction has been taken into account while synthesising the SPM data. Sampling for twenty-four hour duration with a frequency of twice a week has been done for a period of five months (October, 1996 to February, 1997). For impact assessment modelling, the data were converted into monthly mean concentrations. The observed exceedence in SPM varies from 118.2 to 278.3%, 13.12 to 163.3% and I 5.87% at different monitoring sites. An inverse relationship of distance from quarrying and crusher sites with SPM exceedence levels in air is also well documented.